MECOVI : Improving the Survey and Measurement of Living Conditions in Latin America and the Caribbean - Moncada, Gilberto; Lee, Haeduck (World Bank, Washington, DC, 2012)
The MECOVI program --short for "Programa para el Mejoramiento de las Encuestas de Hogares y la Medicion de Condiciones de Vida", a Spanish acronym for the Regional Program for Improvement of the Surveys and Measurement of the Living Conditions in Latin America and the Caribbean.--was launched in 1996, as a joint initiative of the Inter-American Development Bank (IDB), the World Bank, and the United Nations Economic Commission for Latin America and the Caribbean (UN-ECLAC). It was driven by the need to improve the statistical knowledge base on household poverty and living conditions at the household level in the region. The program has two principal components: (1) activities at the country level; and (2) regional activities (training, workshops and organization of the household survey database).